A decade of climate-smart agriculture in major agri-food systems: Earthworm abundance and soil physico-biochemical properties - Jat, Hanuman Sahay; Choudhary, Madhu; Kakraliya, S.; Gora, Manoj K.; Kakraliya, Manish; Kumaran, Vikas V.; Priyanka; Poonia, Tanuja; McDonald, Andrew J.; Jat, Mangi Lal; Sharma, Parbodh Chander; Abdallah, Ahmed M. (MDPI, 2022)
Earthworms (EWs) could be a viable indicator of soil biology and agri-food system management. The influence of climate-smart agriculture (CSA)-based sustainable intensification practices (zero tillage, crop rotations, crop residue retention, and precision water and nutrients application) on earthworms’ (EWs) populations and soil physico-biochemical properties of rice-wheat cropping system in the Indo-Gangetic plains of South Asia was investigated. This study investigates the effect of 10-years adoption of various CSA practices on the abundance of earthworms and physical and biochemical properties of the soil and EWs’ casts (EWC). Five scenarios (Sc) were included: conventionally managed rice-wheat system (farmers’ practices, Sc1), CSA-based rice-wheat-mungbean system with flood irrigation (FI) (Sc2) and subsurface drip irrigation (SDI) (Sc3), CSA-based maize-wheat-mungbean system with FI (Sc4), and SDI (Sc5). Results revealed that EWs were absent under Sc1, while the 10-year adoption of CSA-based scenarios (mean of Sc2–5) increased EWs’ density and biomass to be 257.7 no. m−2 and 36.05 g m−2, respectively. CSA-based maize scenarios (Sc4 and Sc5) attained higher EWs’ density and biomass over rice-based CSA scenarios (Sc2 and Sc4). Also, SDI-based scenarios (Sc3 and Sc5) recorded higher EWs’ density and biomass over FI (Sc2 and Sc4). Maize-based CSA with SDI recorded the highest EWs’ density and EWs’ biomass. The higher total organic carbon in EWC (1.91%) than in the bulk soil of CSA-based scenarios (0.98%) and farmers’ practices (0.65%) suggests the shift of crop residue to a stable SOC (in EWC). EWC contained significant amounts of C and available NPK under CSA practices, which were nil under Sc1. All CSA-based scenarios attained higher enzymes activities over Sc1. CSA-based scenarios, in particular, maize-based scenarios using SDI, improved EWs’ proliferation, SOC, and nutrients storage (in soil and EWC) and showed a better choice for the IGP farmers with respect to C sequestration, soil quality, and nutrient availability.